Certolizumab - Savaş Yaylı (Galenos Publishing House, 2022)
Certolizumab is a Fab fragment of a humanized monoclonal antibody against tumor necrosis factor-alpha (TNF-α). Differing from the other TNF-α inhibitors due to the absence of Fc fragment and pegylation, it binds to both the soluble and transmembrane forms of TNF-α, creating a strong TNF-α blockage. Previously approved for psoriatic arthritis, certolizumab received another approval from FDA in 2018 for the treatment of moderate to severe chronic plaque psoriasis that does not respond to conventional systemic treatments or for which these treatments are contraindicated. Administered via subcutaneous injections, certolizumab also has a low-dose option for patients weighing less than 90 kg. Certolizumab is considered a safe biological drug that can be preferred during pregnancy and lactation.